Grammatical Features of the Third Grade "Reading Book" Texts - Tadjibayeva Nilufar Gayratjon qizi (International Journal on Human-Computing Studies, 2022)
We have developed recommendations for getting acquainted with the popular scientific text of Dilfuza Kamoljonova "Happy Holidays" in the section "Mother is one, the motherland is one" in the third grade textbook, to share experiences.